Phytochemical Screening and Antioxidant Activity Analysis of N-Hexane Extract of Sonneratia alba Mangrove Leaves - Surya, Putu Rissa Almadea; Wijaya, Made Dharmesti; Udiyani, Desak Putu Citra (Biology, Medicine, & Natural Product Chemistry, 2023)
Mangrove plants have been widely used by people in various regions of Indonesia as traditional medicine for the treatment of wounds, fever, diarrhea, and others. Extreme habitat in coastal areas with high salinity and low oxygen level makes mangrove plants produce a variety of unique secondary metabolites and are rich in antioxidants. Although there have been studies on phytochemicals and antioxidant activity conducted, the study of mangroves in Bali, Indonesia, has not been widely explored. This study aims to determine the compounds contained in mangrove leaf extract and their antioxidant activity. The species to be studied is Sonneratia alba, which is commonly found in the Ngurah Rai Mangrove Forest, Bali, Indonesia. In this experimental study, compound extraction was carried out by maceration method using n-hexane solvent. Phytochemical screening using qualitative methods and GC-MS was carried out to determine the phytochemical compounds in the extract, while 1,1-diphenyl-2-picrylhydrazyl (DPPH) method was used to determine antioxidant activity. The result showed that the n-hexane S. alba mangrove leaves extract display strong antioxidant activity with IC50 value of 64.432 Â± 7.675 ppm. The qualitative phytochemical tests showed that the extract contained phenol and steroid, which are known to have antioxidant properties. Moreover, GC-MS analysis showed that there are two compounds with the largest %area namely gamma-sitosterol and dl-alpha-tocopherol (52.88% and 7.77%, respectively), which have been reported to have antioxidant activities. To conclude, these findings demonstrate that n-hexane extract of S. alba mangrove leaves from Ngurah Rai Mangrove Forest, Bali, to have potential antioxidant activity.